Association of Working Status with Clinical Pregnancy and Miscarriage among Women undergoing In Vitro Fertilization: Single-Centre Cross-Sectional Study - Dinara Makhadiyeva; Almaz Ibragimov; Saltanat Baikoshkarova; Milan Terzic; Alpamys Issanov (International Journal of Fertility and Sterility, 2024)
Background: Middle-aged working women represent most patients attending fertility clinics for in vitro fertilization(IVF) treatment. In this study, we aimed to identify the association of women’s working status with clinical pregnancyand miscarriage in the first trimester after IVF treatment.Materials and Methods: In this single-centre cross-sectional study at a private clinic in Kazakhstan, we reviewedelectronic medical records of all IVF with intracytoplasmic sperm injection (ICSI) and fresh embryo transfer (ET) cyclesfrom January 2018 to December 2019 (n=654). 300 cycles in patients with normal ovarian reserve and registeredworking status of a female partner in the medical records were selected for the analysis. The study's primary outcomemeasures were clinical pregnancy rates and clinical miscarriage in the first trimester.Results: 204 women were employed, while 96 were not employed before the start of treatment. The mean age of allpatients was 32.2 ± 4.8 years, ranging from 23 to 46 years. Two-thirds of working women had office-based occupationsemployed as doctors, school and university teachers, accountants, clerks, and managers. One-third of the studyparticipants had manual labor jobs, including service positions and plant workers. There was no association betweenwomen’s working status and clinical pregnancy rate adjusted for age, antral follicle count, history of pelvic adhesiolysis,and embryo development stage at embryo transfer. However, working women had almost five times the risk of thefirst trimester miscarriage compared to non-working women [adjusted odds ratio (aOR) 4.56, 95% confidence interval(CI): 0.52 to 4.96] adjusted for age and number of retrieved oocytes.Conclusion: Women who work before commencing IVF treatment can be reassured of having equal chances of conceptionfollowing the treatment compared to non-working women. The observed risk of first trimester miscarriage inworking women necessitates further research before drawing any conclusions from medical and public health points.